FLUIDIZATE-EXPLOSIVE ORE-FORMING ACTIVIZATION STAGES IN ASPECT OF DIAMONDS AND GOLD METALLOGENY OF THE UKRAINIAN SHIELD CENTRAL PART - YATSENKO, G.; BRATCHUK, O.; YATSENKO, V.; SLYVKO, E.; SHKURENKO, I.; HAYOVSKY, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Some aspects of Lower Proterozoic protoplatforms metallogeny have been considered on the example of Kirovograd block of the Ukrainian Shield. The sources and location conditions of gold and diamonds have been analysed in connection with fluidizate-explosive processes at activization stages in the Precambrian and Phanerozoic.